2014
DOI: 10.1371/journal.pone.0090025
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Protein Kinases Pyk3 and Phg2 as Regulators of the STATc-Mediated Response to Hyperosmolarity

Abstract: Cellular adaptation to changes in environmental osmolarity is crucial for cell survival. In Dictyostelium, STATc is a key regulator of the transcriptional response to hyperosmotic stress. Its phosphorylation and consequent activation is controlled by two signaling branches, one cGMP- and the other Ca2+-dependent, of which many signaling components have yet to be identified. The STATc stress signalling pathway feeds back on itself by upregulating the expression of STATc and STATc-regulated genes. Based on micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…As recently demonstrated, in Dictyostelium cells the Ser448 and Ser747 phosphorylation of the protein-tyrosine phosphatase-3 (PTP3) is induced by a variety of stresses resulting in inhibition of its phosphatase activity and, consequently, maintenance of its substrate, STATc, activity [40]. In agreement with the data from literature, the results showed that after hyperosmotic stress both expression and activity (phosphorylation status at Tyr694) of STAT5 were increased (Fig.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…As recently demonstrated, in Dictyostelium cells the Ser448 and Ser747 phosphorylation of the protein-tyrosine phosphatase-3 (PTP3) is induced by a variety of stresses resulting in inhibition of its phosphatase activity and, consequently, maintenance of its substrate, STATc, activity [40]. In agreement with the data from literature, the results showed that after hyperosmotic stress both expression and activity (phosphorylation status at Tyr694) of STAT5 were increased (Fig.…”
Section: Resultssupporting
confidence: 87%
“…It is well described that when mammalian cells are subjected to osmotic or oxidative stress they respond to such stresses through activation of JAK/STAT signaling pathways and maintenance of its activity through inhibition of protein tyrosine phosphatases such as PTP3. As recently demonstrated, in Dictyostelium cells the Ser448 and Ser747 phosphorylation of the protein-tyrosine phosphatase-3 (PTP3) is induced by a variety of stresses resulting in inhibition of its phosphatase activity and, consequently, maintenance of its substrate, STATc, activity [ 40 ]. In agreement with the data from literature, the results showed that after hyperosmotic stress both expression and activity (phosphorylation status at Tyr694) of STAT5 were increased ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that, in the case of stress but not DIF-1, another kinase is almost fully competent to subsume the function of Pyk2 as an activator of STATc. The logical candidate for this role is Pyk3; it has the most closely related kinase domain in the kinome (51% identity in the kinase domain, Supplemental Figure S4A), it is one of the five TKLs that autophosphorylate on tyrosine when expressed in E. coli , and two entirely independently constructed and analyzed null strains for pyk3 ( pyk3 − strains, Supplemental Figure S2) show a 20–50% reduction in their sorbitol-induced activation of STATc ( Figure 2A ; Vu et al. , 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…Thus drugs that elevate intracellular calcium levels activate STATc, and at least one of them, 2,5,-di(tert-butyl)-1-4-benzohydroquinone (BHQ), leads to increased serine phosphorylation at one of the regulatory sites: S747 ( Figure 1 ). Analysis of a gene disruptant suggests that Phg2, a serine/threonine-specific member of the TKL group, lies in the pathway that represses PTP3 activity by modifying it on S747 ( Figure 1 ; Vu et al. , 2014 ).…”
Section: Introductionmentioning
confidence: 99%